2022
DOI: 10.5670/oceanog.2022.122
|View full text |Cite
|
Sign up to set email alerts
|

Eddies and the Distribution of Eddy Kinetic Energy in the Arctic Ocean

Abstract: Mesoscale eddies are important to many aspects of the dynamics of the Arctic Ocean. Among others, they maintain the halocline and interact with the Atlantic Water circumpolar boundary current through lateral eddy fluxes and shelf-basin exchanges. Mesoscale eddies are also important for transporting biological material and for modifying sea ice distribution. Here, we review what is known about eddies and their impacts in the Arctic Ocean in the context of rapid climate change. Eddy kinetic energy (EKE) is a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 57 publications
5
10
0
Order By: Relevance
“…The highest EKE observed corresponded to the upper continental slope at the AK1‐AK3 moorings (0–15 km of the transect) (Figure 5b). This agrees with previous Arctic Ocean studies, which reported an order of magnitude higher EKE along the continental slopes (depths>1,000 m) than elsewhere (von Appen et al., 2022). North of AK3, the EKE in the ABC flow was weaker and indicates a relatively constant flow throughout the 3‐year record (Figure 5b).…”
Section: Discussionsupporting
confidence: 93%
“…The highest EKE observed corresponded to the upper continental slope at the AK1‐AK3 moorings (0–15 km of the transect) (Figure 5b). This agrees with previous Arctic Ocean studies, which reported an order of magnitude higher EKE along the continental slopes (depths>1,000 m) than elsewhere (von Appen et al., 2022). North of AK3, the EKE in the ABC flow was weaker and indicates a relatively constant flow throughout the 3‐year record (Figure 5b).…”
Section: Discussionsupporting
confidence: 93%
“…The ocean turbulence in our simulations is exclusively generated by shallow melt fronts established in between individual sea ice floes, while the ocean below the mixed layer is mostly quiescent. However, mesoscale eddies in the ocean interior are ubiquitous over the Arctic basin (Dmitrenko et al., 2008; von Appen et al., 2022; Zhao et al., 2014), and have radii ranging between 10 and 60 km, comparable to the size of the largest sea‐ice floes. The surface velocity expression of these mesoscale eddies has the potential to interact with sea‐ice floes and associated melt fronts, and generate submesoscale instabilities through mesoscale‐driven surface frontogenesis (Callies et al., 2016; Lapeyre & Klein, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These errors are derived from floats in ice‐free waters. There is evidence that mesoscale variability is somewhat dampened in ice‐covered waters in the Arctic Ocean (von Appen et al., 2022). This suggests that the error estimates we provide here may be larger than the true errors.…”
Section: Methodsmentioning
confidence: 99%